A Silver‐Copper Alloy as an Oxygen Reduction Electrocatalyst for an Advanced Zinc‐Air Battery. Issue 15 (24th June 2015) - Jin, Yachao; Chen, Fuyi; Lei, Yimin; Wu, Xiaoqiang
Abstract A highly efficient Ag‐Cu electrocatalyst is synthesized by the electrodeposition method and characterized with respect to its catalytic activity in the oxygen reduction reaction (ORR) and its tolerance to carbonate ions in a zinc‐air battery. Cyclic voltammetry and rotating‐disk electrode analyses suggest that the Ag50Cu50 electrocatalyst is 2.5 times more catalytically active in the ORR than a pure Ag catalyst and catalyzes the ORR through a four‐electron pathway. Field‐emission TEM characterization shows that the surface‐roughened Ag‐Cu electrocatalyst comprises small nanoplatelets with diameters of 40–50 nm. Cu atoms are partially alloyed in Ag lattices in these nanoplatelets. The Ag‐Cu electrocatalysts are assembled into the primary and secondary zinc‐air batteries as carbon‐free and binder‐free catalyst layers. The open circuit voltage and the discharge voltage of the primary zinc‐air battery at 20 mA cm−2 are 1.49 and 1.17 V, respectively. The round‐trip efficiency and increased polarization of the rechargeable zinc‐air battery are 56.4 and 0.2 %, respectively, after 100 cycles at 20 mA cm−2. The Ag‐Cu electrocatalyst shows good catalytic activity in the oxygen evolution reaction in an alkaline battery and good tolerance of carbonate ions on the cathode side.